Venous Hypertension, Inflammation and Valve Remodeling - Takase, S.; Pascarella, L.; Lerond, L.; Bergan, J.J.; Schmid-Schönbein, G.W. (European journal of vascular and endovascular surgery, 2004)
Objectives. To identify possible mechanisms for destruction of valves in chronic venous hypertension and the results of treatment with an anti-inflammatory micronized purified flavonoid fraction. Material and methods. The saphenous vein valves in a rat model of venous hypertension caused by a femoral arterial-venous fistula were studied. Studies included femoral venous pressure, valve morphology, femoral venous reflux and selected molecular inflammatory markers as examined by immunohistochemistry. The effects of treatment with the anti-inflammatory micronized purified flavonoid fraction (S 5628, Servier, 50 and 100 mg/kg/day) were investigated. Results. The femoral venous pressure was elevated close to arterial values for a period of 3 weeks. We then examined the morphology of the veins and selected molecular inflammatory markers were assessed. The results show that in this model venous reflux develops in response to venous hyptertension. This can be inhibited by the administration of the anti-inflammatory micronized purified flavonoid fraction (S 5628, Servier, 50 and 100 mg/kg/day). The valve becomes incompetent by a combination of venous dilation and shortening of the valve leaflets. This is not inhibited by treatment with S 5628. The valve leaflets are infiltrated with granulocytes, monocytes and T-lymphocytes, and the endothelial cells express enhanced levels of P-selectin and ICAM-1. Cells in the valves are subject to extensive apoptosis although no enhancement of MMP 2,9 expression could be detected at the three-week time point examined in this study. Conclusions. These results indicate that in this model chronic elevation of venous pressure is associated with an inflammatory reaction in venous valves, a process that may lead to their dysfunction, reflux, and upstream elevation of venous pressure. These effects are mitigated by the anti-inflammatory micronized purified flavonoid fraction in a dose dependent manner.